JASLARDÍŃ KÁSIP TAŃLAWINDA TÁSIR ETIWSHI FAKTORLAR HÁM ORTALÍQ - Matkarimova, M.A. (SCIENCE and SOCIETY, 2023)
The article presents one of the problems of social psychology is the choice of a career by young people, their individual characteristics and influence factors. The influence of parents, teachers and the social environment is discussed on the choice of profession by adolescents.